Powered Wheelbarrow - Molpie, Muhamd Izwan; Norjali, Rasida; Mashori, Sumaiya (Progress in Engineering Application and Technology, 2023)
Studies have shown that most users experience difficulties with the maneuverability of their strollers, particularly in terms of wheelbarrows. These issues are often caused by a variety of factors, such as carrying heavy loads, especially during wet seasons, which can make it difficult to grip the handles and navigate through slippery or uneven terrain. To address these issues, powered wheelbarrows have been developed. These allow for larger loads to be carried with less effort, as the employees only need to exert a small amount of force to move the wheelbarrow smoothly. A Brushless DC Motor is used for the primary part of this project. 350W 24V Brushless DC Motor will be used as the actuator of the entire system to move a wheelbarrow without requiring much workforce. Then, the brushless motor controller is used as the microcontroller for the system. The controller can regulate the motor's speed and the forward/reverse motion of a wheelbarrow. This can improve the overall safety of the wheelbarrow and make it more user-friendly. The powered wheelbarrows will be tested in three different categories: construction, agriculture, and factory. In this project, the load level will be tested on various types of surfaces to evaluate the effect of surface type and load level on the performance of the wheelbarrow. The aim is to determine how the performance or speed of the wheelbarrow when used on various surfaces and the difference in load weight to understand the relationship between the type of surface and load level. This information can be used to improve the design and structural performance of the wheelbarrow.